Investigation of Cortical Thickness Abnormalities in Lithium-Free Adults With Bipolar I Disorder Using Cortical Pattern Matching - Foland-Ross, Lara C.; Thompson, Paul M.; Sugar, Catherine A.; Madsen, Sarah K.; Shen, Jim K.; Penfold, Conor; Ahlf, Kyle; Rasser, Paul E.; Fischer, Jeffrey; Yang, Yilan; Townsend, Jennifer; Bookheimer, Susan Y.; et al. (The American journal of psychiatry, 2011)
Objective:Although several lines of evidence implicate gray matter abnormalities in the prefrontal cortex and anterior cingulate cortex in patients with bipolar disorder, findings have been largely inconsistent across studies. Differences in patients' medication status or mood state or the application of traditional volumetric methods that are insensitive to subtle neuroanatomical differences may have contributed to variations in findings. The authors used MRI in conjunction with cortical pattern matching methods to assess cortical thickness abnormalities in euthymic bipolar patients who were not receiving lithium treatment. Method:Thirty-four lithium-free euthymic patients with bipolar I disorder and 31 healthy comparison subjects underwent MRI scanning. Data were processed to measure cortical gray matter thickness. Thickness maps were spatially normalized using cortical pattern matching and were analyzed to assess illness effects and associations with clinical variables. Results:Relative to healthy comparison subjects, euthymic bipolar patients had significantly thinner gray matter in the left and right prefrontal cortex (Brodmann's areas 11, 10, 8, and 44) and the left anterior cingulate cortex (Brodmann's areas 24/32). Thinning in these regions was more pronounced in patients with a history of psychosis. No areas of thicker cortex were detected in bipolar patients relative to healthy comparison subjects. Conclusions:Using a technique that is highly sensitive to subtle neuroanatomical differences, significant regional cortical thinning was found in lithium-free euthymic patients with bipolar disorder.